Ocean carbon sequestration: Particle fragmentation by copepods as a significant unrecognised factor?: Explicitly representing the role of copepods in biogeochemical models may fundamentally improve understanding of future ocean carbon storage. (11th November 2020) - Mayor, Daniel J.; Gentleman, Wendy C.; Anderson, Thomas R.
Abstract: Ocean biology helps regulate global climate by fixing atmospheric CO2 and exporting it to deep waters as sinking detrital particles. New observations demonstrate that particle fragmentation is the principal factor controlling the depth to which these particles penetrate the ocean's interior, and hence how long the constituent carbon is sequestered from the atmosphere. The underlying cause is, however, poorly understood. We speculate that small, particle‐associated copepods, which intercept and inadvertently break up sinking particles as they search for attached protistan prey, are the principle agents of fragmentation in the ocean. We explore this idea using a new marine ecosystem model. Results indicate that explicitly representing particle fragmentation by copepods in biogeochemical models offers a step change in our ability to understand the future evolution of biologically‐mediated ocean carbon storage. Our findings highlight the need for improved understanding of the distribution, abundance, ecology and physiology of particle‐associated copepods. Abstract : Small copepods in the ocean's twilight zone (100–1000 m) inadvertently fragment sinking particles of detritus when consuming particle‐attached protists. Results from our new ecosystem model suggest that this activity may significantly influence particle sinking and remineralisation rates, and ultimately affect how long the constituent carbon is sequestered from the atmosphere.